On the Racialization of the Moroccan ‘Other’ in Orientalist Romance - Moussaoui, Abdelghani (International Journal of Language and Literary Studies, 2024)
This paper offers an understanding of the discourse of difference in relation to the themes of race and identity in Rebecca Stratton’s bestselling romance The Silken Cage. It unravels how Morocco, as a subject and a culture, is racialized in British orientalist romance to underpin the discourse of the centre/periphery duality in cross-cultural encounters. The Silken Cage is worthy of study due to its interest in how the Moroccan ‘Other’ is turned into a commodity in popular romance. After a postcolonial analysis of the suggested romance, it was found that racial conceptions of the Moroccan Other’s identity are at large contingent on racial hierarchies. The novel seems, at first glance, to negotiate the construction of racial identities and thereby dismantle the system of binarism between the ‘Self’ and the ‘Other.’ However, the author’s emphasis on the ambivalence of the oriental subjects articulates a continued need for racial sameness and the denial of difference. Needless to say, given that racial hybridity is a prerequisite for the courtship to be successful reveals that Stratton resists cross-cultural difference. It can be thus argued that Stratton’s romance is an interracial ground where racial differences are not welcomed to legitimize Western hegemony and domination over the Orient.